Relating electrical conduction of alluvial sediments to textural properties and pore‐fluid conductivity. (27th January 2014) - Mele, Mauro; Inzoli, Silvia; Giudici, Mauro; Bersezio, Riccardo
ABSTRACT Electrical conductivity of alluvial sediments depends on litho‐textural properties, fluid saturation and porewater conductivity. Therefore, for hydrostratigraphic applications of direct current resistivity methods in porous sedimentary aquifers, it can be useful to characterize the prevailing mechanisms of electrical conduction (electrolytic or shale conduction) according to the litho‐textural properties and to the porewater characteristics. An experimental device and a measurement protocol were developed and applied to collect data on eight samples of alluvial sediments from the Po plain (Northern Italy), characterized by different grain‐size distribution, and fully saturated with porewater of variable conductivity. The bulk electrical conductivities obtained with the laboratory tests were interpreted with a classical two‐component model, which requires the identification of the intrinsic conductivity of clay particles and the effective porosity for each sample, and with a three‐component model. The latter is based on the two endmember mechanisms, surface and electrolytic conduction, but takes into account also the interaction between dissolved ions in the pores and the fluid‐grain interface. The experimental data and their interpretation with the phenomenological models show that the volumetric ratio between coarse and fine grains is a simple but effective parameter to determine the electrical behaviour of clastic hydrofacies at the scale of the representative elementary volume.